Femto- and nanosecond pulse duration dependence of the single-shot ablation threshold and multiple-shot morphology change of poly L-lactic acid in deep ultraviolet regime. (12th June 2019) - Shibuya, Tatsunori; Satoh, Daisuke; Tanaka, Masahito; Ogawa, Hiroshi; Kuroda, Ryunosuke
Abstract: Laser processing is a common method used to shape various structures of biodegradable polymers. In this study, we demonstrate PLLA processing with intense deep ultraviolet (DUV) pulses at 266 nm and compare the processing properties using a nanosecond DUV laser. Results allow comparison of the single-shot ablation thresholds and multiple-shot morphology of both the femtosecond and nanosecond DUV laser. For sing-shot experiments, the ablation threshold of femtosecond laser is, at least, one order of magnitude lower than that of nanosecond laser. For multiple-shot experiments, the result provides superior quality of the crater morphology in the DUV femtosecond regime.